MENGGALI MISKONSEPSI SISWA SD TENTANG TATA SURYA SECARA LISAN DALAM BAHASA DAYAK SUAID - Stepanus Jumadi; Haratua Tiur Maria S; Hamdani Hamdani (Universitas Tanjungpura, 2018)
AbstractThis study was purposed to explore elementary school students’ misconceptions about solar-system orally, in Dayak Suaid language. The semi-structured interview has been used to explore students’ misconceptions. This study was involved 15 six-grade students in SD N 11 Jerenjang. The collected data were qualitatively-analyzed by comparing students’ conceptions and scientists’ conceptions to earn students’ misconceptions. Results of this study showed that average of students misconceptions equal to 53,33% for definition of solar system; 66,67% for the sun as a star; 33,33% for the closest to the farthest planets from the sun; 13,33% for the characteristic of planet based on the picture; and 46,67% for the definition of satellite. The misconceptions that happened was, several students, notice that solar system is a collection of planets that surround earth or sun. Lots of student mention that the sun is not a star because its shape was round not pentagon and did not appear at night. Several students mentioned that planet is earth or palapa, based on the picture . The other students notice that satellite is a signal, a moon, an earth, a transmitter on space, and signal transmitter. Similar research was suggested to explore students’ misconceptions based on the